Hukum Menyegerakan Zakat Harta dalam Surat Edaran Menteri Agama Nomor 6 Tahun 2020 Perspektif Dlawabith Maslahah Said Ramadhan Al-Buthi - Muhammad Khatibul Umam; Abbas Arfan; Burhanuddin Susamto (Fakultas Syariah IAIN madura, 2022)
Menyegerakan zakat harta yang tertuang dalam Surat Edaran Menteri Agama No.06 Tahun 2020 dilakukan untuk kemaslahatan umat. Teori dlawabith al-Maslahah d al-Buthi dirasa pelu menjadi alat pengukur tentang Batasan seuatu dikatakan sebagai maslahah. Maka dari itu timbulah rumusan masalah sebagai berikut: pertama, bagaimana hukum menyegerakan zakat dalam Undang-Undang zakat?. Kedua, bagaimana kesesuaian menyegerakan zakat perpsektif teori Dlawabith al-Maslahah Al-Buthi. Penelitian ini merpakan penelitian normative dengan menggunakan pendekatan konseptual atau pustaka (Conceptual Approach). Hasil penelitan ini mempunyai kesimpulan bahwa dalam Undang-Undang zakat, bahwa untuk melakukan pembayaran zakat harta harus mencapai Nishab dan haul. Kedua, dalam teori Dlawabith al-Maslahah al-Buthi jika menyegerakan zakat harta demi kemaslahatan dan tidak bertentangan dengan tujuan syariah, al-Qur’an dan Hadis. (hastening the zakat of assets contained in the Circular of the Minister of Religion No. 06 of 2020 is carried out for the benefit of the people. The theory of dlawabith al-Maslahah d al-Buthi feels the need to be a measuring tool about the boundaries of something said to be maslahah. Therefore, the formulation of the problem arises as follows: first, how is the law hastening zakat in the zakat law? Second, how is the suitability of accelerating zakat from the perspective of Dlawabith al-Maslahah Al-Buthi theory. This research is a normative research using a conceptual approach or literature (Conceptual Approach). The results of this research have the conclusion that in the Zakat Act, that in order to pay zakat assets, it must reach the Nishab and haul. Second, in the theory of Dlawabith al-Maslahah al-Buthi, if it hastens the zakat of wealth for the benefit and does not conflict with the objectives of sharia, the Koran and Hadith.)